2017
DOI: 10.1186/s13068-017-0973-z
|View full text |Cite
|
Sign up to set email alerts
|

Designer biomass for next-generation biorefineries: leveraging recent insights into xylan structure and biosynthesis

Abstract: Xylans are the most abundant noncellulosic polysaccharides in lignified secondary cell walls of woody dicots and in both primary and secondary cell walls of grasses. These polysaccharides, which comprise 20–35% of terrestrial biomass, present major challenges for the efficient microbial bioconversion of lignocellulosic feedstocks to fuels and other value-added products. Xylans play a significant role in the recalcitrance of biomass to degradation, and their bioconversion requires metabolic pathways that are di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
112
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 117 publications
(192 reference statements)
1
112
0
Order By: Relevance
“…Xylan is an abundant and complex cell wall component in plants, particularly in commelinid primary walls and in secondary cell walls of all angiosperms (Scheller & Ulvskov, 2010). It consists of a polymeric backbone of 1,4-b-linked D-xylose (Xyl) decorated mainly with acetyl groups, and is further substituted by L-arabinofuranose (Araf ) in commelinids or methylated or unmethylated D-glucuronic acid (GlcA) in noncommelinid angiosperms (Scheller & Ulvskov, 2010;Smith et al, 2017;Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Xylan is an abundant and complex cell wall component in plants, particularly in commelinid primary walls and in secondary cell walls of all angiosperms (Scheller & Ulvskov, 2010). It consists of a polymeric backbone of 1,4-b-linked D-xylose (Xyl) decorated mainly with acetyl groups, and is further substituted by L-arabinofuranose (Araf ) in commelinids or methylated or unmethylated D-glucuronic acid (GlcA) in noncommelinid angiosperms (Scheller & Ulvskov, 2010;Smith et al, 2017;Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes catalyse the biosynthesis of the xylan backbone, transferring nucleotide sugars to the growing AX chain within the Golgi apparatus. Two members of the glycosyltransferase family 43 (GT43), IRREGULAR XYLEM9 (IRX9) and IRX14 proteins, and one member of GT47, IRX10, are implicated in the biosynthesis of the xylan backbone, but the specific role is not completely established (Brown et al ., ; Smith et al ., ). Subsequent works confirmed that IRX10 is the β‐1,4‐xylan xylosyl transferase responsible for xylan polymer extension, transferring xylosyl residues from UDP‐xylose to xylooligosaccharides at the reducing end, whereas IRX9 and IRX14 are accessory proteins involved in the elongation of the xylan backbone and are structural components of the functioning xylan synthase complex (XSC).…”
Section: Tailoring Xylan Structurementioning
confidence: 97%
“…Subsequent works confirmed that IRX10 is the β‐1,4‐xylan xylosyl transferase responsible for xylan polymer extension, transferring xylosyl residues from UDP‐xylose to xylooligosaccharides at the reducing end, whereas IRX9 and IRX14 are accessory proteins involved in the elongation of the xylan backbone and are structural components of the functioning xylan synthase complex (XSC). Additionally, glucuronosyltransferases (GUX) from the GT8 family and arabinosyltransferases (XAT) from the GT61 family are responsible for the addition of glucuronosyl and arabinosyl on the xylan backbone, respectively (Smith et al ., ).…”
Section: Tailoring Xylan Structurementioning
confidence: 97%
See 2 more Smart Citations